The association between rs12807809 polymorphism in neurogranin gene and risk of schizophrenia: A meta-analysis - Jin, Lu (Medicine (Baltimore), 2019)
BACKGROUND: The correlation between single nucleotide polymorphism (SNP) rs12807809 in Neurogranin (NRGN) gene and Schizophrenia (SCZ) was investigated by several studies, whereas the results were conflicting. Thus, we performed the present meta-analysis to combine and analyze the available studies in order to provide a more accurate result on the association of rs12807809 polymorphism in NRGN gene and SCZ vulnerability. METHODS: A comprehensive retrieval in PubMed, EMBASE, Web of Science, Cochrane Library and Wanfang was performed for relevant studies on the relationship of rs12807809 polymorphism and SCZ. Summary odds ratios (OR) with 95% confidence interval (95% CI) were calculated in allelic, homozygous, heterozygous, dominant and recessive model to appraise the association. RESULTS: The meta-analysis included 8 studies containing 12552 SCZ cases and 34783 controls. The results showed a statistically significant correlation between SCZ and rs12807809 polymorphism in overall population in allelic model (OR = 1.10, 95%CI 1.04–1.17). However, subgroup analysis indicated the association only existed in Caucasians but not Asian. CONCLUSION: The results of present meta-analysis suggested significant association between SNP rs12807809 in NRGN gene and SCZ susceptibility in Caucasians but not Asians.